KERJASAMA GURU BIMBINGAN DAN KONSELING DENGAN GURU MATA PELAJARAN DALAM MENGEMBANGKAN CARA BELAJAR SISWA - Adriani, Melisa; Khairani, Khairani; Sukmawati, Indah (Universitas Negeri Padang, 2013)
Effective guidance services need cooperation of BK teachers with other personnel at the school. In fact, it’s still less cooperation BK teachers with subject teachers in BK services at the schools. This study aims to reveal cooperation the BK teacher with subject teachers in developing the way of learning student. Forms of quantitative research is descriptive type. The results revealed that BK teacher cooperation with subject teachers in developing the way of learning student good average.